PENGARUH WAKTU PENYADAPAN TERHADAP PRODUKSI LATEKS TANAMAN KARET RAKYAT KLON PB 260 - Sutrisno, Sutrisno; Syafrinal, Syafrinal (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research objectives are to find out the appropriate tapping time and its effect on the latex production of PB 260 rubber plantation so that the highest production would be gained. The experiment was carried out in the Bukit Selanjut Village, Kelayang Districts, Indragiri Hulu Regency, Riau Province. The study was conducted for 1 month from September to October 2016. The study arranged experimentally using Completely Randomized Block Design with 7 treatments and 3 replications then obtained 21 experimental units. The treatment of rubber plantation tapping time used is K1: 05.00 am, K2: 05.30 am, K3: 06.00 am, K4: 06.30 am, K5: 07.00 am, K6: 07.30 am and the K7: 08.00 am. The parameters were observed drip duration of latex droplet, latex volume and dry rubber content. Data was analyzed statistically using ANOVA and tested by Duncan’s New Multiple Range Test (DNMRT) at 5% level. The research result showed that different tapping time effect the parameters drip duration of latex, latex volume and the dry rubber content. Tapping the rubber plant at 06.00 am was the best time for tapping because it creates the longest latex droplet which was 78,38 minutes, highest latex volume was 81,73 ml and highest dry rubber content was 68,26%. Keywords: Hevea brasiliensis Muell Arg, PB 260 clone, tapping time